Transparansi dan Akuntabilitas dalam Pengelolaan Dana Desa (Studi Kasus Desa Giri Sasak Kecamatan Kuripan) - Haeniah Haeniah; Animah Animah; Yusli Mariadi (Akbis: Media Riset Akuntansi dan Bisnis, 2022)
This study aims to find out how the form of transparency and accountability carried out by the Giri Sasak Village Government in managing its finances, especially those sourced from village funds. Because the amount of village funds allocated every year is used by all parties, both the government above it and the community in the village. These principles are indispensable in the management of village funds in order to minimize the occurrence of corruption, fraud and abuse of power and budget starting from the planning, implementation, administration, reporting, and accountability stages.This study uses a qualitative method with a descriptive approach, and the data collection uses observation, interviews, and documentation. The method of analysis in this study, namely; data reduction, data presentation and then drawing conclusions. The results of this study indicate that the Giri Sasak Village Government in its financial management process is in accordance with the Minister of Home Affairs Regulation Number 20 of 2018 The conclusions of the research carried out can be seen through five stages. The stages of planning, implementation, administration, as well as reporting and accountability have been carried out in a transparent and accountable manner. This can be seen through every meeting that always involves elements of the community, providing access to information, recording income and expenses, and so on.